Talking Stick Learning Model Guide Illustrated Storybook to Improve Speaking Skills of Third Grade Elementary School Students: Indonesia - Widya Karmila Achmad; Agustiana Putu Vionita; Gusti Ayu Putu Sukma Trisna; I Ketut Gading (Jurnal Media dan Teknologi Pendidikan, 2025)
This research is a type of development research motivated by the low speaking skills of third-grade elementary school students. This development research aims to describe the validity, practicality, and effectiveness of the product developed. In this study, the development model used is the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The trial subjects were 55 third-grade elementary school students. To collect data in this study, interviews, observations, and questionnaires were used. The results of the media validity test were categorized as valid, in addition to the results of the analysis by expert practitioners, it could be assessed as very good. Based on the conclusion, the speaking stick learning model guide for picture story books was declared suitable for use in learning activities. This development research has an impact on improving the skills of third-grade students, which in turn has an impact on improving other skills. This study has limitations, namely the use of digital book-based media also requires supporting devices such as projectors or laptops, which may not be evenly available in all schools. Overall, this media is declared effective for improving the speaking skills of third-grade elementary school students.